The Effectiveness Of Application Of Tuberculosis Pocketbook To Improve Knowledge On The Implementationand Prevention Oftuberculosis Inthe Family Experiment Study Of Modify TBC Pocket Book Application - Aris Fitriyani; Widjijati Widjijati; Siti Mulidah (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Type of study is quasi-experiment with non randomized design with pretest-posttest control group design. The numbers of sample are 100 respondents consisting of 2 groups: the control group who received PPTI pocket book and the treatment group who received modification pocket book. The research was conducted at the health center working area of Banyumas Sokaraja II in 2012. An analytical technique used in this study is the Wilcoxon test. The results showed that the level of knowledge of the family in the treatment and prevention of tuberculosis in the working area Sokaraja II District Health Center Sokaraja Banyumas given before and after results obtained PPTI Handbook p = 0.001, while the results obtained modification pocketbook 0.000. Therefore it can be said that the granting of a modification pocketbook is more effective than PPTI pocketbook because the respondents said the modification pocketbook easier to understand language modification and more interesting because it is accompanied by pictures than PPTI pocketbook that only contains written information that respondents feel bored and lazy to read it. Thus the necessary modification pocketbook reproduced and distributed to the public both in the working area and outside the working area Sokaraja Health Center II in the implementation and prevention of TB disease in order to assist the TB-free world by 2050.